Comprehensive educational plan for patients with epilepsy and comorbidity (EDU-COM): a pragmatic randomised trial. Issue 8 (8th January 2014) - Beretta, Simone; Beghi, Ettore; Messina, Paolo; Gerardi, Francesca; Pescini, Francesca; La Licata, Andrea; Specchio, Luigi; Ferrara, Mariangela; Canevini, Maria Paola; Turner, Katherine; La Briola, Francesca; Franceschetti, Silvana; et al.
Abstract : Background: The impact of educational strategies in the management of adverse treatment effects and drug interactions in adult patients with epilepsy with comorbidities remains undetermined. Objective: The EDU-COM study is a randomised, pragmatic trial investigating the effect of a patient-tailored educational plan in patients with epilepsy with comorbidity. Methods: 174 adult patients with epilepsy with chronic comorbidities, multiple-drug therapy and reporting at least one adverse treatment effect and/or drug interaction at study entry were randomly assigned to the educational plan or usual care. The primary endpoint was the number of patients becoming free from adverse treatment events and/or drug interactions after a 6-month follow-up. The number of adverse treatment events and drug interactions, health-related quality of life (HRQOL) summary score changes and the monetary costs of medical contacts and drugs were assessed as secondary outcomes. Results: The primary endpoint was met by 44.0% of patients receiving the educational plan versus 28.9% of those on usual care (p=0.0399). The control group reported a significantly higher risk not to meet successfully the primary endpoint at the end of the study: OR (95% CI) of 2.29 (1.03 to 5.09). A separate analysis on drug adverse effects and drug interactions showed that the latter were more sensitive to the effect of educational treatment. Quality of life and costs were not significantly different in the two groups. Conclusions: A patient-tailored educational strategy is effective in reducing drug-related problems (particularly drug interactions) in epilepsy patients with chronic comorbidities, without adding significant monetary costs. Registered at ClinicalTrials.gov, identifier NCT01804322, (http://www.clinicaltrials.gov ).